Mutual impact of wild and cultured Atlantic salmon in Norway - Egidius, Emmy; Hansen, Lars P.; Jonsson, Bror; Nævdal, Gunnar (ICES Journal of Marine Science, 1991)
The development and current status of the fish-farming industry, enhancement, and sea ranching of salmon in Norway are briefly described, and an account is given of the natural salmon river populations in different parts of the country. Records of cultured salmon in the open sea, coastal waters, and rivers are reviewed, as are migration studies on liberated farmed salmon. The recent development in farming and ocean ranching has led to an increased proportion of reared fish in nature. Survival and migration of such fish appear to be strongly dependent on season. Adults escaping in summer seem to behave like homeless fish, and enter rivers at random for spawning. Fish escaping at the smolt stage return to the area from which they escaped and enter rivers in the same area for spawning. Diseases common to wild and cultured populations are described and discussed in relation to possible intcrtransmission. The fluke Gyrodactylus salaris has been spread to 32 rivers, probably by stocking fish from infected hatcheries. The salmon lice, which normally are considered harmless to wild salmon, have been shown to affect salmon reared in net pens. Bacterial and fungal diseases are found among free-living as well as among cultured salmon; wild populations may act as reservoirs for the disease agents. The actual and potential effects of cultured salmon on natural gene pools are discussed. Escaped salmon may cause gene flow between cultured and wild populations, thus reducing the variation between natural populations. Hybridization, with possible hybrid vigour and short-term adaptation, is another potential consequence, which may reduce the capacity of the population to adapt to local environments. Initiatives to protect natural gene pools are described and briefly discussed. These include the technical improvement of farming facilities, the establishment of gene banks (now in operation), restrictions on the transfer of living material, and the use of indigenous fish for enhancement and establishment of areas protected from fish ...